Risk and association of HLA with oxcarbazepine-induced cutaneous adverse reactions in Asians. (3rd January 2017) - Chen, Chun-Bing; Hsiao, Yi-Hsin; Wu, Tony; Hsih, Mo-Song; Tassaneeyakul, Wichittra; Jorns, Teekayu P.; Sukasem, Chonlaphat; Hsu, Chien-Ning; Su, Shih-Chi; Chang, Wan-Chun; Hui, Rosaline Chung-Yee; Chu, Chia-Yu; et al.
Abstract : Objective: To investigate the risk and genetic association of oxcarbazepine-induced cutaneous adverse reactions (OXC-cADRs), including Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN), in Asian populations (Chinese and Thai). Methods: We prospectively enrolled patients with OXC-cADRs in Taiwan and Thailand from 2006 to 2014, and analyzed the clinical course, latent period, drug dosage, organ involvement, complications, and mortality. We also investigated the carrier rate of HLA-B*15:02 and HLA-A*31:01 of patients with OXC-cADRs and compared to OXC-tolerant controls. The incidence of OXC-SJS/TEN was compared with carbamazepine (CBZ)–induced SJS/TEN according to the nationwide population dataset from the Taiwan National Health Insurance Research Database. Results: We enrolled 50 patients with OXC-cADRs, including 20 OXC-SJS/TEN and 6  drug reaction with eosinophilia and systemic symptoms, of Chinese patients from Taiwan and Thai patients from Thailand. OXC-cADRs presented with less clinical severity including limited skin detachment (all ≦5%) and no mortality. There was a significant association between HLA-B*15:02 and OXC-SJS ( p = 1.87 × 10 −10 ; odds ratio 27.90; 95% confidence interval [CI] 7.84–99.23) in Chinese and this significant association was also observed in Thai patients. The positive and negative predictive values of HLA-B*15:02 for OXC-SJS/TEN were 0.73% and 99.97%, respectively. HLA-A*31:01 was not associated with OXC-cADRs. The incidence and mortality of OXC-SJS/TEN was lower than CBZ-STS/TEN in new users ( p = 0.003; relative risk 0.212; 95% CI 0.077–0.584). Conclusions: Our findings suggest that HLA-B*15:02 is significantly associated with OXC-SJS in Asian populations (Chinese and Thai). However, the severity and incidence of OXC-SJS/TEN are less than that of CBZ-SJS/TEN. The need for preemptive HLA-B*15:02 screening should be evaluated further.